Developing a Urinary Catheter with Anti-Biofilm Coated Surface Using Phyto-Assisted Synthesis of Zinc Oxide Nanoparticles - Goda RM; Maghrabi IA; El-Badawy MF; Kabel AM; Omar AA; El-Morsi RM; Ramadan HA; Shohayeb MM (Infection and Drug Resistance)
Reham M Goda,1,* Ibrahim A Maghrabi,2 Mohamed F El-Badawy,3,* Ahmed M Kabel,4 Alaa A Omar,5 Rasha M El-Morsi,1 Heba A Ramadan,1 Mohamed M Shohayeb1 1Department of Microbiology and Immunology, Faculty of Pharmacy, Delta University for Science and Technology, International Coastal Road, Gamasa, 11152, Egypt; 2Department of Clinical Pharmacy, College of Pharmacy, Taif University, Taif, 21944, Saudi Arabia; 3Department of Microbiology and Immunology, Faculty of Pharmacy, University of Sadat City, Sadat City, Menoufia, 32897, Egypt; 4Pharmacology Department, Faculty of Medicine, Tanta University, Tanta, 31527, Egypt; 5Nanomedicine Research Unit, Delta University for Science and Technology, International Coastal Road, Gamasa, 11152, Egypt*These authors contributed equally to this workCorrespondence: Mohamed F El-Badawy, Department of Microbiology and Immunology, Faculty of Pharmacy, University of Sadat City, Sadat city, 32897, Menoufia, Egypt, Tel +20-103-205-9964, Email Mohamed.Elbadawy@fop.usc.edu.egBackground: Biofilm-related infections represent one of the major challenging health problems that enhances antimicrobial resistance with subsequent treatment failure of catheter-associated urinary tract infections (CAUTIs).Aim: This study aimed to employ and comprehensively characterize the use of nanoparticles to inhibit bacterial biofilm formation. Zinc oxide nanoparticles (ZnO-NPs) are considered one of the most important biofilm inhibitors.Methods: The current study aimed to characterize the influence of the bioreductive green synthesis of ZnO-NPs using pomegranate peel extract on bacterial colonization to protect against urinary catheter infections. ZnO-NPs were investigated for their physicochemical properties using UV, FTIR, Dynamic light scattering, and TEM. Catheters were coated with ZnO-NPs using Pistacia lentiscus (mastic), and the slow release of free zinc ions (Zn+2) from, the ZnO-NPs-coated catheters, was evaluated using the ICP-AES technique.Results: The current study revealed that catheter coated by ZnO-NPs exhibited a sustained antibiofilm activity against biofilm-forming and antibiotic-resistant clinical isolates of Staphylococcus epidermidis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, and Pseudomonas aeruginosa strains.Conclusion: The present study supports the efficiency of ZnO-NPs as a good candidate for prevention of biofilm formation.Keywords: urinary catheters, biofilm, bacterial colonization, zinc oxide nanoparticles, catheter associated infection